Is the T-ligament a ligament? A histological study in equine cadaver forelimbs. (October 2020) - Hontoir, F.; Paques, F.; Simon, V.; Balau, B.; Nicaise, C.; Clegg, P.; Dugdale, A.; Vandeweerd, J.M.
Abstract: Foot pain is a frequent cause of lameness in horses and can involve multiple structures within the hoof. The T-ligament (an anatomical structure connecting the synovium of the distal interphalangeal joint, the digital flexor tendon sheath and the navicular bursa) is poorly described. Five pairs of equine cadaver distal forelimbs were collected from a slaughterhouse. Sagittal sections (medial, middle and lateral) were obtained and processed with Haematoxylin Eosin Safran, Unna's Orcein, and Picrosirius red stains. Histological assessment revealed that the T-ligament was covered by the surrounding synovia of the distal interphalangeal joint, the digital flexor tendon sheath and the navicular bursa. Its collagen content was lower (30.01%±10.15) than that of the collateral sesamoidean ligament (89.48%±5.8; P  = .0008) and the middle phalanx (85.72%±3.67; P = .0008). Under polarized light microscopy, it showed a slight heterogeneous pattern of birefringence, with angle-related changes. Elastic fibres were more numerous (21.76%±8.72) than in the collateral sesamoidean ligament (0.28%±0.45), or deep digital flexor tendon (0.04%±0.02); and were more densely packed. Mean cell count was higher for the T-ligament than for other tissues ( P  = .0007). Blood vessels were identified in the T-ligament and were penetrating the deep digital flexor tendon (8/10 limbs, 5/5 horses). In conclusion, the T-ligament looked like a vinculum for the deep digital flexor tendon, with a central elastic core, surrounding loose connective tissue and blood vessels. It is not a ligament. Its clinical relevance still needs to be determined. Highlights: The T-ligament (transverse lamina, proximal sesamoid ligament) connects the deep digital flexor tendon & the middle phalanx. It connects indirectly the proximal border of the navicular bone via the junction of both collateral sesamoidean ligaments. It consists of a core of densely packed elastic fibres surrounded by loose connective tissue & blood vessels. It is covered by surrounding synovia of the equine digital extremity. This ligament is a dorsal vinculum for the deep digital flexor tendon.